Efektifitas Rumah Singgah Bagi Anak Jalanan di Kota Surabaya (Studi Kasus Rumah Singgah Sanggar Alang-Alang) - Haning, Emiliana; Yulianti, Tri (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Judging from the problems of street children in big cities in Indonesia more particularly in Surabaya, the purpose of this study is to know the level of effectiveness of providing shelter for street children in Surabaya City with a case study of a stopover house Alang-Alang. This study used a qualitative descriptive approach with the type of case study. Primary data obtained through observation and in-depth interview, while secondary data obtained through documentation. Based on the result of field research, the lessons given by the houses of gallery houses tostreet children have not achieved the effectiveness measures that include production, efficiency, satisfaction, and development. Effectiveness means the right target and meet the overall target objectives. Inadequate facilities, inadequate facilities and insufficient funds to meet household needs. The participation of the government and the community to continue to support shelter for street children is needed for street children to learn can reduce the number of children working on the streets. Keywords: effectiveness shelter for street children